PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL DAN MEDIA BERBASIS KOMPUTER PADA MATERI POKOK PEMBANGUNAN BERKELANJUTAN KELAS XI SMA NEGERI 7 BANJARMASIN TAHUN AJARAN 2014/2015 - Yeni Febriani; Karunia Puji Hastuti; Parida Angriani (JPG (Jurnal Pendidikan Geografi), 2015)
Title in this research is “Difference Of Student’s Learning Result Whose Taught Using Audio Visual Media and Computer Based Media On The Subject Matter Of Sustainable Development At Class XI SMA 7 Banjarmasin Academic Year 2014/2015". This research aims to find out the difference of student’s learning result whose taught using audio visual media and computer based media on the subject matter of sustainable development at class XI SMA 7 Banjarmasin academic year 2014/2015.Population of this research is all students at class XI IPS in SMA Negeri 7 Banjarmasin. The sample obtained used purpossive sample technique, the sample is all students at class XI IPS 2 and class XI IPS 3. The first experiment class is XI IPS 2 whose taught using computer based media, and the second class using audio visual media. Primary data obtained throuh observation in the field, and the values of the pre test and post test. Secondary data obtained from the study of document and literature. The technique of data analysis is percentage technique and t test analysis.The result calculation which used t test analysis techniques both at pre-test and post-test showed that thitung < ttable 5%. The calculation results showed that there was no significant difference between student learning result are taught using audio visual media and computer based media, then Ha is rejected and H0 accepted. Keywords: Difference, Student’s learning result, Media Audio Visual,Computer Based Media